COHERENCE BETWEEN THE THEORY OF MIND AND PERSONALITY TRAITS IN THE CONDITIONS OF NORM AND IN DEPENDENCE ON PSYCHOACTIVE SUBSTANCES - Telcharov, Oleksandr (International Journal of Innovative Technologies in Social Science, 2021)
The term Theory of Mind (ToM) refers to the cognitive ability to understand the persons’ own and others’ intentions, emotions, feelings, beliefs, and so on. This psychological ability has been studied mainly in the context of normal development, in the conditions of normal ontogenesis, as well as on the example of animals, children with atypical development, adults with certain mental disorders. There are also studies related to some specifics of ToM in people dependent to alcohol. The aim of the article is to establish correlations between ToM and personality traits in the conditions of norm and dependence on psychoactive substances (PAS). The study was conducted on 98 individuals. 42 are people dependent on PAS and are stand at the initial stage of recovery, 15 people are dependent on PAS at a later stage of recovery and 41 people which are a group of conditional norm. The nonparametric method of r-Spearman rank correlation coefficient is used. As a result, established a number of links between ToM and personality traits during the comparison the data of persons dependent on PAS and conditional norm persons It is setted that the dependence on PAS has a negative effect on ToM. ToM is related the most to the fifth factor “Expressiveness-Practice” of the 5PFQ Personal Questionnaire. The second external correlate of ToM, which is expressed more in the early stages of recovery from PAS, can be considered as the second factor of the Personality Questionnaire 5PFQ "Attachment-Isolation". The assumption has been made that the ToMC scale has the most valuable biological correlates and the strongest expression with personality traits. The age trait is strongly related to the ToM scales linearly.